Measuring the Diphoton Coupling of a 750 GeV Resonance - Fichet, S. [UNESP]; von Gersdorff, G.; Royon, C. (Amer Physical Soc, 2016)
A slight excess has been observed in the first data of photon-photon events at the 13 TeV Large Hadron Collider that might be interpreted as a hint of physics beyond the standard model. We show that a completely model-independent measurement of the photon-photon coupling of a putative 750 GeV resonance is possible using the forward proton detectors scheduled at ATLAS and CMS.